Pertangungjawaban Pidana Tim Anggaran Pemerintah Daerah Dalam Penetapan RKA-SKPD Yang Menimbulkan Kerugian Negara - Weldy Vienando Lopulisa; Juanrico Alfaromona Sumarezs Titahelu; Erwin Ubwarin (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The corruption case at the Ambon City Environmental and Solid Waste Service (DLHP) is getting hotly discussed by the Ambon city public. DLHP Ambon City, where one of the points that became the focus of the prosecution's indictment was the discrepancy in the standard analysis of spending on the fuel oil procurement project for the waste fleet belonging to the Ambon city government.Purposes of the Research: To know the form of abuse of authority by officials that result in state losses. And knowing that the Investigator Formulated the Elements of Abuse of Authority for the Crime of Corruption, the Ambon City Environment and Waste Office. Methods of the Research: The research method used in analyzing and discussing is normative juridical, a normative study must of course use a statutory approach because it is careful that various legal rules are the focus of a research. The legal materials used are primary, secondary and tertiary legal materials.Results of the Research: The results of the study point to the decision Number 32/Pid.Sus-TPK/2021/P stating that the defendant has been indicted by the public prosecutor and has been legally and convincingly proven guilty of committing a criminal act of corruption, as regulated and subject to criminal penalties in Article 3 in conjunction with Article 18 of the Republic of Indonesia Law. Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption as amended by Law Number R.I. 20 of 2001 concerning Amendments to Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption in conjunction with Article 55 paragraph (1) to 1 of the Criminal Code in the SUBSIDAIR ACCOUNT.